2007
DOI: 10.3318/bioe.2007.107.3.157
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Cycles in Long Irish Meteorological Series

Abstract: We have analysed the trends in four long meteorological time series from Armagh Observatory and compared them with series available from other Irish sites. We find that although maximum and minimum temperatures have risen in line with global averages, minima have risen faster than maxima, thereby reducing the daily temperature range. The total number of hours of bright sunshine has fallen since 1885 at the four sites studied, which is consistent with both a rise in cloudiness and the fall in the daily temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 8 publications
2
13
2
Order By: Relevance
“…Evidence that the results presented in this study are of more than purely local significance is provided by the similarity of climate trends measured at Armagh to those at three other Irish sites with long‐term records: in all four series the periodicities appear to be linked with those of the North Atlantic Oscillation [ Butler et al , 2007]. On a larger spatial scale the increase in mean annual air temperature measured at Armagh, 0.74°C over the last century, was similar to the mean for the land surfaces of the Northern Hemisphere over the same period, 0.63°C [ Intergovernmental Panel on Climate Change ( IPCC ), 2007].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Evidence that the results presented in this study are of more than purely local significance is provided by the similarity of climate trends measured at Armagh to those at three other Irish sites with long‐term records: in all four series the periodicities appear to be linked with those of the North Atlantic Oscillation [ Butler et al , 2007]. On a larger spatial scale the increase in mean annual air temperature measured at Armagh, 0.74°C over the last century, was similar to the mean for the land surfaces of the Northern Hemisphere over the same period, 0.63°C [ Intergovernmental Panel on Climate Change ( IPCC ), 2007].…”
Section: Discussionmentioning
confidence: 84%
“…Multilinear regression analysis showed that the highest correlations and greatest climate sensitivity to both long‐ and short‐wave radiation occurred in the winter months; by contrast there was no significant relationship between the sum of the two radiation fluxes and temperatures, neither for annual nor seasonal relationships. In this connection it is noted that seasonal differences were found in the rates of the air temperature increases measured at Armagh; during the autumn and spring months the increase in temperatures exceeded those occurring in the winter and summer months and in the annual values [ Butler et al , 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Wavelet analysis has previously been brought into use in climate studies (e.g. Lau and Weng, 1995;Torrence and Compo, 1997;Baliunas et al, 1997;Isaksson et al, 2005, Butler et al, 2007, but until now the technique only has received limited interest from the climate community in general. The modest interest may partly be explained by the intense focus on analytic climate modelling, and partly by the fact that most papers on wavelet analysis tend to employ a difficult mathematical language.…”
Section: Wavelet Analysesmentioning
confidence: 99%
“…In White Lough, the sediment is well dated, and Anderson et al. (2012) argue that the cycles in biogenic silica recorded in the sediments can be linked to the NAO through the correlation between the summer precipitation record from the nearby Armagh Observatory and the NAO (Butler, Garcia‐Suarez & Palle, 2007). However, from the perspective of the sediment record at White Lough, the in‐lake response is probably mediated by catchment soil processes and the competition between diatoms and cyanobacteria for nutrients.…”
Section: Disentangling Climate Impactsmentioning
confidence: 99%